Long run relationship between Malaysian stock market and agriculture sector - Muhammad, Junaina; Ghuslan, Mohamad Iruwan; Jusoff, Kamaruzaman (Cabells USA, 2009)
Since independence, agriculture has been Malaysia’s primary economic activity and has been the major source of national income (Danilah et.al, 2004). However, in 1987, the manufacturing sector takes over as the premier sector in the economy growth (BNM, 1989). Recently, in the ninth Malaysia plan period, the government has given a new emphasis to agriculture sector. Thus, this paper is to investigate the long-run relationship between Malaysian stock market and agriculture sector performances during 15 years period from 1990 to 2005. The results suggest that Malaysian stock market and agriculture sector have a positive long- run relationship.